Online booking of hotels in Mauritius - Bibi Adiilah Futloo.
Online Hotel Booking is a system that has been developed to give the convenience to the user in saving their time in finding their desired hotel through internet. The user can browse the web site of Online Hotel Booking (MauritianLodging.com) to get information about the hotel's background and services and also make the reservation as well. This interactive web page gives the advantage to user to get new information about the interesting hotel that can be visited in Mauritius. The user can choose their rest place depend on their taste and budget. This project documentation has included some concepts, methodologies, techniques in designing some essential diagrams, such as Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), Structure Charts, Data Dictionary etc. The objective is to clear defined of the system and provide a good understanding about the current and proposed system. This project is developed using a Windows based platform, and the system is run through the internet. The interface of the system is written by using Macromedia Dreamweaver 4, Active Server Page (ASP) and for validation purposes Java Script. SQL Server 7.0 for the database that will be used.